Sphingosine Kinase 2 Regulates Aryl Hydrocarbon Receptor Nuclear Translocation and Target Gene Activation - Yokoyama, Shigetoshi; Koo, Imhoi; Aibara, Daisuke; Tian, Yuan; Murray, Iain A.; Collins, Stephanie L.; Coslo, Denise M.; Kono, Mari; Peters, Jeffrey M.; Proia, Richard L.; Gonzalez, Frank J.; Perdew, Gary H.; et al. (Advanced science, 2024)
Sphingolipids play vital roles in metabolism and regulation. Previously, the aryl hydrocarbon receptor (AHR), a ligand‐activated transcription factor, was reported to directly regulate ceramide synthesis genes by binding to their promoters. Herein, sphingosine kinase 2 (SPHK2), responsible for producing sphingosine‐1‐phosphate (S1P), was found to interact with AHR through LXXLL motifs, influencing AHR nuclear localization. Through mutagenesis and co‐transfection studies, AHR activation and subsequent nuclear translocation was hindered by SPHK2 LXXLL mutants or SPHK2 lacking a nuclear localization signal (NLS). Similarly, an NLS‐deficient AHR mutant impaired SPHK2 nuclear translocation. Silencing SPHK2 reduced AHR expression and its target gene CYP1A1, while SPHK2 overexpression enhanced AHR activity. SPHK2 was found enriched on the CYP1A1 promoter, underscoring its role in AHR target gene activation. Additionally, S1P rapidly increased AHR expression at both the mRNA and protein levels and promoted AHR recruitment to the CYP1A1 promoter. Using mouse models, AHR deficiency compromised SPHK2 nuclear translocation, illustrating a critical interaction where SPHK2 facilitates AHR nuclear localization and supports a positive feedback loop between AHR and sphingolipid enzyme activity in the nucleus. These findings highlight a novel function of SPHK2 in regulating AHR activity and gene expression. Schematic illustration of the dual function of SPHK2. (A) SPHK2 functions as a cofactor for the AHR/ARNT heterodimer on the DRE‐containing promoter region of the CYP1A1 gene. (B) SPHK2, S1P, and AHR establish a positive feedback mechanism for ceramide de novo biosynthesis metabolism. S1P also enhances AHR recruitment to DREs.